The Efektivitas Rhizobakteria dan Pupuk Kotoran Kambing pada Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Novi Saskia; Dewi Firnia; Putra Utama; Abdul Hasyim Sodiq (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Shallot plants come in various types and are essential in preparing food, driving the need for increased production. In Indonesia, one popular variety is Bima Brebes. This study aims to accelerate the growth and productivity of Bima Brebes shallots using rhizobacteria and goat manure fertilizer. An unexpected group design was employed in the April–June experimental study, and two factors were subjected to ANOVA and the Duncan Multiple Range Test (DMRT) at a 5% significant level. Rhizobacteria (R) at concentrations of 0 mililiter, 5 mililiter, 10 mililiter, and 15 mililiter was the first factor. The second factor was goat manure fertilizer (K) at doses of 0 ton/hektar, 10 ton/hektar, 20 ton/hektar, and 30 ton/hektar, with three replicates, resulting in a total of 48 plants. Plant height, leaf count, tuber diameter, number of tubers per clump, and weight of wet and dry tubers per clump were among the tracked variables. A 15 ml/liter rhizobacteria concentration significantly improved plant growth, achieving a plant height of 37.04 cm, 6.79 tubers per clump, 85.83 g wet mass per cluster, and 50.33 g dry mass per cluster. Similarly, a goat manure fertilizer dose of 30 t/ha positively impacted bulb weight, increasing it to 39.17 g. He combined rhizobacteria and goat manure fertilizer to enhance plant growth by supplying critical micronutrients and promoting vegetative development. There was a notable interaction between rhizobacteria concentration and goat manure fertilizer.